Fibre morphology and physical properties of 10-year-old Sentang (Azadirachta excelsa) planted from rooted cuttings and seedlings. - A.S. , Nordahlia; S., Ani; Ashaari, Zaidon; Sahri , Mohd Hamami (2011)

(untitled)
Fibre morphology and physical properties of 10-year-old sentang (Azadirachta excelsa) planted from rooted cuttings and seedlings were determined and compared. Results obtained would determine the appropriate planting technique of sentang to produce high quality timber. Wood produced from rooted-cutting tree had longer and larger fibres as well as thicker fibre walls compared with wood from seedlings. With regard to shrinkage, seedling-planted wood had lower longitudinal and volumetric shrinkages than rooted-cutting wood. However, the radial and tangential shrinkages did not differ significantly. Fibre morphology decreased significantly with height, while basic densities and shrinkages decreased from the bottom to the middle of the trunk and then increased towards the top in both types of wood.